2021
DOI: 10.1089/env.2021.0021
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Distribution of Environmental Health Threats and Hazards in Washington State Using a Cumulative Environmental Inequality Index

Abstract: Background: Environmental racism, community stressors, and age-related susceptibility play a significant role in environmental inequality. The goal of this article was to use an inequality index (II) to assess the level of equality in environmental threats and hazards based on race, poverty, and age in Washington State. Methods: Using the Washington Environmental Health Disparities Map, we quantified the level of disproportionate burdens on communities with greater populations of people of color, people in pov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…Multiple studies have shown [35][36][37] that BIPOC individuals will be more impacted by climate change and environmental degradation in the coming years. And, throughout the environmental movement, BIPOC people may have been left out of the conversations in some spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown [35][36][37] that BIPOC individuals will be more impacted by climate change and environmental degradation in the coming years. And, throughout the environmental movement, BIPOC people may have been left out of the conversations in some spaces.…”
Section: Discussionmentioning
confidence: 99%